Drag the tiles to the boxes to form correct pairs. Not all tiles will be used.
Match the function with its inverse.


File ATTACHED
THANK YOU

Drag the tiles to the boxes to form correct pairs Not all tiles will be used Match the function with its inverse File ATTACHED THANK YOU class=

Respuesta :

Answer:

Part 1) [tex]f(x)=\frac{2x-1}{x+2}[/tex] -------> [tex]f^{-1}(x)=\frac{-2x-1}{x-2}[/tex]

Part 2) [tex]f(x)=\frac{x-1}{2x+1}[/tex] -------> [tex]f^{-1}(x)=\frac{-x-1}{2x-1}[/tex]

Part 3) [tex]f(x)=\frac{2x+1}{2x-1}[/tex] -----> [tex]f^{-1}(x)=\frac{x+1}{2(x-1)}[/tex]

Part 4) [tex]f(x)=\frac{x+2}{-2x+1}[/tex] ----> [tex]f^{-1}(x)=\frac{x-2}{2x+1}[/tex]

Part 5) [tex]f(x)=\frac{x+2}{x-1}[/tex] -------> [tex]f^{-1}(x)=\frac{x+2}{x-1}[/tex]

Step-by-step explanation:

Part 1) we have

[tex]f(x)=\frac{2x-1}{x+2}[/tex]

Find the inverse  

Let

y=f(x)

[tex]y=\frac{2x-1}{x+2}[/tex]

Exchange the variables x for y and t for x

[tex]x=\frac{2y-1}{y+2}[/tex]

Isolate the variable y

[tex]x=\frac{2y-1}{y+2}\\ \\ xy+2x=2y-1\\ \\xy-2y=-2x-1\\ \\y[x-2]=-2x-1\\ \\y=\frac{-2x-1}{x-2}[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=\frac{-2x-1}{x-2}[/tex]

Part 2) we have

[tex]f(x)=\frac{x-1}{2x+1}[/tex]

Find the inverse  

Let

y=f(x)

[tex]y=\frac{x-1}{2x+1}[/tex]

Exchange the variables x for y and t for x

[tex]x=\frac{y-1}{2y+1}[/tex]

Isolate the variable y

[tex]x=\frac{y-1}{2y+1}\\ \\2xy+x=y-1\\ \\2xy-y=-x-1\\ \\y[2x-1]=-x-1\\ \\y=\frac{-x-1}{2x-1}[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=\frac{-x-1}{2x-1}[/tex]

Part 3) we have

[tex]f(x)=\frac{2x+1}{2x-1}[/tex]

Find the inverse  

Let

y=f(x)

[tex]y=\frac{2x+1}{2x-1}[/tex]

Exchange the variables x for y and t for x

[tex]x=\frac{2y+1}{2y-1}[/tex]

Isolate the variable y

[tex]x=\frac{2y+1}{2y-1}\\ \\2xy-x=2y+1\\ \\2xy-2y=x+1\\ \\y[2x-2]=x+1\\ \\y=\frac{x+1}{2(x-1)}[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=\frac{x+1}{2(x-1)}[/tex]

Part 4) we have

[tex]f(x)=\frac{x+2}{-2x+1}[/tex]

Find the inverse  

Let

y=f(x)

[tex]y=\frac{x+2}{-2x+1}[/tex]

Exchange the variables x for y and t for x

[tex]x=\frac{y+2}{-2y+1}[/tex]

Isolate the variable y

[tex]x=\frac{y+2}{-2y+1}\\ \\-2xy+x=y+2\\ \\-2xy-y=-x+2\\ \\y[-2x-1]=-x+2\\ \\y=\frac{-x+2}{-2x-1} \\ \\y=\frac{x-2}{2x+1}[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=\frac{x-2}{2x+1}[/tex]

Part 5) we have

[tex]f(x)=\frac{x+2}{x-1}[/tex]

Find the inverse  

Let

y=f(x)

[tex]y=\frac{x+2}{x-1}[/tex]

Exchange the variables x for y and t for x

[tex]x=\frac{y+2}{y-1}[/tex]

Isolate the variable y

[tex]x=\frac{y+2}{y-1}\\ \\xy-x=y+2\\ \\xy-y=x+2\\ \\y[x-1]=x+2\\ \\y=\frac{x+2}{x-1}[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=\frac{x+2}{x-1}[/tex]